Numerical Simulation of Highly Efficient Cs2TiI6 Based Cd Free Perovskites Solar Cell with the Help of Optimized ETL and HTL Using SCAPS-1D Software - Halim, Md Abdul; Islam, Md Shafiqul; Hossain, Md Momin; Khan, Md Yakub Ali (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
In order to provide the best photovoltaic application, this paper examines the physical, optical, and electrical aspects of Cesium Titanium (IV) based single halide Perovskite absorption materials. Perovskite solar cell for scavenging renewable energy, has grown more and more necessary in the context of the diversification of the use of natural resources. Due to its efficient band gap of 1.8 eV, Cs2TiI6 has become a desirable contender for today's thin-film solar cell. This article shows the spectrum responses of a planar Au/FTO/C60/Cs2TiI6/CH3NH3SnI3/Al based structure where CH3NH3SnI3 is used as a Hole transport layer (HTL) and C60 and FTO are utilized as Electron transport layers (ETL) under 300K temperature conditions. This research demonstrates that employing Fluorine doped Tin Oxide (FTO) and Ultrathin Fullerene (C60) as Electron transport layer charge extraction can be achieved. FTO provides high transmission, strong conductivity, and good adherence for the deposited layers. When used in a coevaporated perovskite solar cell, a C60 layer with an ideal thickness less than 15 nm improves charge extraction. This article tried to avoid cadmium for solar cell generation due to its toxicity on environment. The simulation included detailed configuration optimization for the thickness of the absorber layer, HTL, ETL, defect density, Wavelength, temperature, and series resistance. In this work the Power Conversion Efficiency (?), Fill Factor (FF), Open-circuit Voltage (Voc), J-V Curve, Quantum Efficiency and Short-circuit current (Jsc) have been measured by varying thickness of absorber layer in the range of 1µm to 6 µm. Energy harvesting effectiveness, cost-effectiveness of perovskite solar cells is all impacted by their PCE, which is a crucial characteristic. The key variables that define a perovskite solar cell's performance are the Voc and fill factor (FF). When the voltage is zero, the solar cell can produce its maximum current, which is represented by the (Isc). The optimized perovskite solar cell shows a power conversion efficiency of 21.8429% when the absorber layer thickness is 4µm and electron transport layer thickness is 0.6µm.